Association of comorbid somatic pathology with fat distribution type and body mass index in men - S. V. Iankovskaia; E. G. Novikova; E. A. Epanchintseva; B. B. Pinkhasov; V. G. Selyatitskaya (Сибирский научный медицинский журнал, 2020)
The purpose of the study was to investigate the effect of overweight, obesity and fat distribution type on the severity of comorbid somatic pathology in men. Material and methods. 216 men, aged from 22 to 78 years, who were patients of therapeutic clinic from 2018 to 2019 years, were observed. Height, body weight, waist (WC) and hip (HC) circumference were measured using standard anthropometric procedures, and then WC/HC and body mass index (BMI) were calculated. Clinical signs of aging were estimated by using the AMS questionnaire. The CIRS was scored from the medical records after hospitalization. Results and discussion. It was shown that overweight and obesity increase the burden of cardiovascular, endocrine and general comorbidity in men. Nevertheless, the burden of cardiovascular pathology did not differ between overweight and obesity men. The contribution of fat distribution type in separate BMI-groups is different. The upper fat distribution type in normal body weight increases the burden of vascular pathology, in overweight – vascular pathology and endocrine system, in obesity – cardiovascular pathology, and general comorbidity in men. Conclusion. Thus, the BMI ≥ 25 kg/m2 is associated with an increase burden of cardiovascular, endocrine and general comorbidity and upper fat distribution type increases the burden of vascular pathology in men.